1970
DOI: 10.1136/gut.11.6.506
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in ankylosing spondylitis

Abstract: SUMMARY Routine detailed gastroenterological investigations were performed in a series of 47 ankylosing spondylitics. Evidence of chronic inflammatory bowel disease was found in eight patients, a prevalence of 17 %. Unsuspected bowel disease was found in the absence of symptoms in three of these patients.The association between ulcerative colitis and ankylosing spondylitis has been well documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1
1

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 22 publications
0
7
1
1
Order By: Relevance
“…The large majority of the patients suffered from CD (76 %) and not UC. This is in contrast with results from previously published data (Jayson and Bouchier, 1968;Jayson et al, 1970;Brewerton et al, 1973), and also from our own data and the recent observation by Woodrow that UC patients possess HLA B27 more frequently than patients suffering from CD (J. C. Woodrow et al, unpublished). However, we have no reason to believe that the CD preponderance has occurred by a selection bias.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The large majority of the patients suffered from CD (76 %) and not UC. This is in contrast with results from previously published data (Jayson and Bouchier, 1968;Jayson et al, 1970;Brewerton et al, 1973), and also from our own data and the recent observation by Woodrow that UC patients possess HLA B27 more frequently than patients suffering from CD (J. C. Woodrow et al, unpublished). However, we have no reason to believe that the CD preponderance has occurred by a selection bias.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well known that the incidence of inflammatory bowel disease (IBD) is increased in patients suffering from ankylosing spondylitis (AS) (Romanus, 1953;Steinberg and Story, 1957;Wilkinson and Bywaters, 1958;McBride et al, 1963;Jayson and Bouchier, 1968;Jayson et al, 1970;Meuwissen et al, 1978). On the other hand, there is an increased frequency of AS in IBD (Acheson, 1960;Moll et al, 1974;Dekker-Saeys, 1977).…”
mentioning
confidence: 99%
“…Так, в 1970 г. были опубликованы результаты исследования M. Jayson и соавт. [14], которые оценили частоту поражения дистальных отделов ЖКТ у 47 больных достоверным (по Римским критериям) АС. В ходе эндоскопического исследования у 8 (17%) больных были выявлены четкие признаки ЯК, причем у трех паци-ентов -при полном отсутствии каких-либо симптомов, указывающих на патологию ЖКТ.…”
Section: таблицаunclassified
“…Numerous studies have demonstrated that there is an association between ankylosing spondylitis and ulcerative colitis (Steinberg and Storey, 1957;Wilkinson and Bywaters, 1958;Fernandez-Herlihy, 1959;Zvaifler and Martel, 1960;Acheson, 1960;McBride, King, Baikie, Crean, and Sircus, 1963;Wright and Watkinson, 1965;Jayson, Salmon, and Harrison, 1970). The prevalence of these diseases in combination appears to be at least ten and perhaps fifty times greater than would be expected if the association was by chance, on the basis of estimates of prevalence in normal populations (Kellgren, 1964;Evans and Acheson, 1965;Ansell and Lawrence, 1966).…”
mentioning
confidence: 99%